Cryptic species of Archinome (Annelida: Amphinomida) from vents and seeps - Borda, Elizabeth; Kudenov, Jerry D.; Chevaldonné, Pierre; Blake, James A.; Desbruyeres, Daniel; Fabri, Marie-Claire; Hourdez, Stéphane; Pleijel, Fredrik; Shank, Timothy M.; Wilson, Nerida G.; Schulze, Anja; Rouse, Greg W. (Proceedings of the Royal Society B: Biological Sciences, 2013)
Since its description from the Galapagos Rift in the mid-1980s, Archinome rosacea has been recorded at hydrothermal vents in the Pacific, Atlantic and Indian Oceans. Only recently was a second species described from the Pacific Antarctic Ridge. We inferred the identities and evolutionary relationships of Archinome representatives sampled from across the hydrothermal vent range of the genus, which is now extended to cold methane seeps. Species delimitation using mitochondrial cytochrome c oxidase subunit I (COI) recovered up to six lineages, whereas concatenated datasets (COI, 16S, 28S and ITS1) supported only four or five of these as clades. Morphological approaches alone were inconclusive to verify the identities of species owing to the lack of discrete diagnostic characters. We recognize five Archinome species, with three that are new to science. The new species, designated based on molecular evidence alone, include: Archinome levinae n. sp., which occurs at both vents and seeps in the east Pacific, Archinome tethyana n. sp., which inhabits Atlantic vents and Archinome jasoni n. sp., also present in the Atlantic, and whose distribution extends to the Indian and southwest Pacific Oceans. Biogeographic connections between vents and seeps are highlighted, as are potential evolutionary links among populations from vent fields located in the east Pacific and Atlantic Oceans, and Atlantic and Indian Oceans; the latter presented for the first time.